RECORDS OF SIX SPECIES OF CARANGIDS FROM THE SOUTHWEST COAST OF INDIA - Sreenivasan, P V (Indian Journal of Fisheries, 2011)
Fishes of the family Carangidae are widely distributed along both thecoasts of India and form about 2% of the total marine fish landings of thiscountry. At Vizhinjam area, along the south west coast of India, there exists aprosperous fishery for carangids which form 15-16% of the total annual catch.